Plants from Urban Parks as Valuable Cosmetic Ingredients: Green Extraction, Chemical Composition and Activity - Marijan Marijan; Jasna Jablan; Lejsa Jakupović; Mario Jug; Eva Marguí; Rogerta Dalipi; Emanuele Sangiorgi; Marijana Zovko Končić (Agronomy, 2022)
The research on the possibilities of using biowaste from urban green areas is scarce. In this work, four plants, widely distributed in urban parks in Central Europe (Lotus corniculatus, Medicago lupulina, Knautia arvensis and Plantago major) were extracted using eco-friendly solvents based either on aqueous cyclodextrin solutions (hydroxypropyl-β-cyclodextrin or γ-cyclodextrin) or natural deep eutectic solvents based on glycerol, betaine and glucose. Metal content was determined using total reflection X-ray fluorescence (TXRF). The content of selected metabolites was determined using UV-VIS spectrophotometric methods and HPLC. Skin-related bioactivity was assessed using tyrosinase and elastase inhibition assays. The selected plants contained metals beneficial for skin health, such as zinc and calcium, while having a low content of toxic heavy metals. The extracts contained the bioactive phenolics such as quercetin, kaempferol, luteolin and apigenin. L. corniculatus was the most potent tyrosinase inhibitor, while K. arvensis showed the most pronounced elastase inhibitory activity. The employed solvents actively contributed to the observed bioactivity. The results indicate that the biowaste obtained from urban parks represents an ecologically acceptable alternative to conventional cultivation for the preparation of ecologically acceptable, high-value cosmetic products.